2019
DOI: 10.1101/743534
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of crowding on the diversity of expanding populations

Abstract: Crowding effects are key to the self-organization of densely packed cellular assemblies, such as biofilms, solid tumors, and developing tissues. When cells grow and divide they push each other apart, remodeling the structure and extent of the populations range. It has recently been shown that crowding effects also couple the evolutionary fate of neighboring cells, thereby weakening the strength of natural selection. However, the impact of crowding on neutral processes remains unclear. Here, we quantify the gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…In addition, genetic drift may be favored because the number of cells that are actually growing might be substantially smaller than the census population (e.g., if bacterial replication were restricted to the very bottom of the follicle) (Hartl and Clark, 2006). In the case of a narrow growth region, physical crowding of cells inside a pore (Jahns and Alexeyev, 2014;Plewig et al, 2019) may exclude beneficial mutants from the growth layer (Schreck et al, 2019;Karita et al, 2021). These proposed mechanisms emphasize how host anatomy has the potential to suppress selective forces and tip the balance toward more neutral outcomes.…”
Section: Skin Pores Promote Intraspecies Diversity Via Neutral Processesmentioning
confidence: 99%
“…In addition, genetic drift may be favored because the number of cells that are actually growing might be substantially smaller than the census population (e.g., if bacterial replication were restricted to the very bottom of the follicle) (Hartl and Clark, 2006). In the case of a narrow growth region, physical crowding of cells inside a pore (Jahns and Alexeyev, 2014;Plewig et al, 2019) may exclude beneficial mutants from the growth layer (Schreck et al, 2019;Karita et al, 2021). These proposed mechanisms emphasize how host anatomy has the potential to suppress selective forces and tip the balance toward more neutral outcomes.…”
Section: Skin Pores Promote Intraspecies Diversity Via Neutral Processesmentioning
confidence: 99%
“…if bacterial replication were restricted to the very bottom of the follicle) (Hartl and Clark, 2006). In the case of a narrow growth region, physical crowding of cells inside a pore (Jahns and Alexeyev, 2014;Plewig et al, 2019) may exclude beneficial mutants from the growth layer (Schreck et al, 2019). These proposed mechanisms emphasize how host anatomy has the potential to suppress selective forces and tip the balance toward more neutral outcomes.…”
Section: Role Of Skin Pores In the Balance Of Neutral And Adaptive Evolutionmentioning
confidence: 99%
“…It is likely that physical effects observed in studies of lateral range expansions [67][68][69][70] also play a role in the upward growth of unconfined biofilms. Previous studies found that proliferating cells in crowded environments interact mechanically [71][72][73], pushing cells towards the expanding cell front.…”
Section: Limited Invasion Via Contact Killingmentioning
confidence: 99%